THE INFLUENCE OF OCCUPATIONAL HEALTH AND SAFETY PROGRAMS ON WORK MOTIVATION AND EMPLOYEE PERFORMANCE AT MEDIKA MANDIRI FOUNDATION - Feiby Jessicha Umboh; Andri Tilaar, Pingkan Pinontoan, Quinthia Manitik, Natalia Tooy (CV. Adiba Aisha Amira, 2025)
Occupational health safety strategies are able to generate work motivation and have an impact on employee performance, problems felt by an employee with a work environment that is less conducive so that work motivation is reduced and employee performance is less productive. How does the Occupational Health and Safety Program affect employee work motivation and performance at the Medika Mandiri Foundation.The method of the research is Explanatory research.The RSquare value in the regression equation is 0.000, so it can be said that the occupational health safety program variable has an impact on employee performance variables. The moderating variable (work motivation) in the second regression equation, the RSquare value increases by 0.094, so it can be concluded that the work motivation variable can strengthen the impact of the occupational safety and health program on employee performance.The occupational health safety program is at a good level, work motivation is at a high level and employee performance is at a high level. The research results show that there is no fire protection system and danger signs have not been installed in the Medika Mandiri Foundation area.